FORMS, METHODS, TOOLS, AND DIDACTIC SUPPORT FOR ENHANCING PRACTICAL COMPETENCE OF PHYSICS STUDENTS THROUGH AN INTEGRATIVE APPROACH - Erkin Bakhronovich Mustafayev (European Science Publishing, 2025)
This article examines the core concepts of the integrative approach in physics education, emphasizing its interconnectedness with teaching forms, instructional methods, and didactic tools. It analyzes both theoretical and practical dimensions of integrated instruction, particularly focusing on establishing interdisciplinary connections within the learning process and utilizing modern information technologies to develop students’ scientific reasoning and hands-on skills. The study further highlights strategies for modernizing the content of physics education in alignment with current educational demands through the implementation of integrative teaching practices.
Keywords: Physics education, integrative approach, interactive methods, instructional formats, teaching aids, interdisciplinary integration, practical competence, AR/VR technologies.